1999
DOI: 10.1016/s0014-5793(99)00967-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of haploid germ cell‐specific tektin cDNA and analysis of the protein in mouse testis

Abstract: Tektins are a class of proteins that form filamentous polymers in the walls of ciliary and flagellar microtubules. We report here the molecular cloning of a new member of the tektin family, tektin-t, identified from a mouse haploid germ cellspecific cDNA library. Tektin-t mRNA encodes a protein of 430 deduced amino acids possessing RSNVELCRD, the conserved sequence of tektin family proteins. Western blotting showed a single band having a molecular weight of 86 kDa in the mouse testis. Immunohistochemistry of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 31 publications
0
72
0
Order By: Relevance
“…In the present study, we report the isolation of a cDNA encoding a testis-speci®c OAZ named OAZ-t from a haploid germ cell-speci®c cDNA library (Iguchi et al 1999). OAZ-t mRNA was exclusively expressed in haploid germ cells.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the present study, we report the isolation of a cDNA encoding a testis-speci®c OAZ named OAZ-t from a haploid germ cell-speci®c cDNA library (Iguchi et al 1999). OAZ-t mRNA was exclusively expressed in haploid germ cells.…”
Section: Introductionmentioning
confidence: 91%
“…From a subtracted cDNA library enriched with haploid speci®c testicular cDNAs (Iguchi et al 1999), we have isolated a cDNA clone named TISP-15 (Transcript Increased in Spermiogenesis) containing a sequence homologous to somatic ornithine decarboxylase antizyme 1 (OAZ1). To isolate the full length cDNA clone, a 35-day-old testis cDNA library (2´10 5 c.f.u.)…”
Section: Molecular Cloning Of the Oaz-t Genementioning
confidence: 99%
“…Previously, we isolated cDNA clones that are specifically expressed in mouse haploid germ cells from the subtracted cDNA library (7). Many of these haploid germ cell-specific genes are thought to be involved in the differentiation process of spermiogenesis and/or in sperm function (7)(8)(9)(10)(11)(12)(13)(14)(15). We report here the characterization of a novel RBCC (RING finger, B-box type zinc finger, and coiled-coil domain) motif family gene named haprin (from haploid germ cell-specific RBCC protein), which was cloned from a subtracted cDNA library.…”
mentioning
confidence: 99%
“…It has been demonstrated that tektins participated in the assembly of axonemal microtubules and offered stability to axonemal microtubules [29]. Tektins are a highly conserved family of flagellar and ciliary proteins in many species from invertebrate to higher species, such as Chlamydomonas, sea urchins, zebrafish, hedgehog, rodents, and humans [18,19,28,30,31]. In mammals, tektins exist in the testis, brain, retina, and other tissues containing ciliated cells [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Bhilawadikar R et al [17] found that tektin-t levels were positively associated with sperm motility parameters, fertilization rate, embryo quality, and pregnancy rate. The human tektin-t (or h-tekB1 or Tektin-2) gene has been cloned [18][19][20], showing a specific expression in testis, and precisely localized in flagella of mature sperm. The localization of this protein and its association with sperm motility make it a good candidate gene for research into the causes of AZS.…”
Section: Introductionmentioning
confidence: 99%